2010
DOI: 10.1140/epjb/e2010-10305-8
|View full text |Cite
|
Sign up to set email alerts
|

Adiabaticity conditions for volatility smile in Black-Scholes pricing model

Abstract: Our derivation of the distribution function for future returns is based on the risk neutral approach which gives a functional dependence for the European call (put) option price, C(K), given the strike price, K, and the distribution function of the returns. We derive this distribution function using for C(K) a Black-Scholes (BS) expression with volatility, σ, in the form of a volatility smile. We show that this approach based on a volatility smile leads to relative minima for the distribution function ("bad" p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…We repeat the fitting procedure considering the volatility smile for different days, currencies and time to maturity T (Table I), then we analyze the relations between the fitting parameters. As already observed in [8], the following relation between n, T, g holds:…”
Section: Volatility Smile: Analysis Of Actual Market Datasupporting
confidence: 53%
See 4 more Smart Citations
“…We repeat the fitting procedure considering the volatility smile for different days, currencies and time to maturity T (Table I), then we analyze the relations between the fitting parameters. As already observed in [8], the following relation between n, T, g holds:…”
Section: Volatility Smile: Analysis Of Actual Market Datasupporting
confidence: 53%
“…We started from the pricing equation of the Black-Scholes model for an European call and we considered the effect of the VS correction on the implied PDF. Our approach comes from statistical physics and it is related to the adiabatic interpretation in [8]. We showed that similar fits of a VS could imply strong differences on the implied returns PDF with obvious consequences on the risk estimation.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations